2021
DOI: 10.3390/biomedicines9111646
|View full text |Cite
|
Sign up to set email alerts
|

ATP and Tri-Polyphosphate (TPP) Suppress Protein Aggregate Growth by a Supercharging Mechanism

Abstract: A common strategy to increase aggregation resistance is through rational mutagenesis to supercharge proteins, which leads to high colloidal stability, but often has the undesirable effect of lowering conformational stability. We show this trade-off can be overcome by using small multivalent polyphosphate ions, adenosine triphosphate (ATP) and tripolyphosphate (TPP) as excipients. These ions are equally effective at suppressing aggregation of ovalbumin and bovine serum albumin (BSA) upon thermal stress as monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 68 publications
(107 reference statements)
1
13
0
Order By: Relevance
“…As such, while binding affinities for TPP in sites III, V, and VI could not be determined, we suspect similar strengths of interaction with the protein for TPP and ATP, where the predominant mode of interaction occurs through phosphate groups. This is also evident from overlaying the precipitation boundaries (Figure A,B), protein–protein interaction (Figure C,D), and ζ-potential profiles (Figure E,F) for ATP versus TPP and from the almost identical effectiveness of ATP and TPP at preventing the aggregation of globular proteins under thermal stress. , …”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…As such, while binding affinities for TPP in sites III, V, and VI could not be determined, we suspect similar strengths of interaction with the protein for TPP and ATP, where the predominant mode of interaction occurs through phosphate groups. This is also evident from overlaying the precipitation boundaries (Figure A,B), protein–protein interaction (Figure C,D), and ζ-potential profiles (Figure E,F) for ATP versus TPP and from the almost identical effectiveness of ATP and TPP at preventing the aggregation of globular proteins under thermal stress. , …”
Section: Discussionmentioning
confidence: 65%
“…For natively folded proteins, molecular simulations indicate that binding to loop regions leads to a reduction in their flexibility. Because these groups are often the most susceptible to unfolding upon heating, it has been hypothesized that ATP binding not only increases the protein’s thermal stability but the unfolded regions are less likely to associate due to preferential interactions with ATP clusters. , On the other hand, we showed that ATP or TPP binds to negatively charged proteins, leading to an overcharging effect and an increase in colloidal stability, which slows down aggregate growth rates . In contrast, for positively charged proteins like lysozyme and the IDP histatin-5, low concentrations of TPP have the opposite effect of causing protein precipitation. , Similarly, ATP has been shown to increase fibril formation for a series of basic IDPs, as well as an insulin fragment conjugated to octalysine .…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations